Age-Dependent Effects of Chronic Stress on Zebrafish Behavior and Regeneration - Henríquez Martínez, Angie; Ávila, Laura C.; Pulido, María A.; Ardila, Yeferzon A.; Akle, Veronica; Bloch, Natasha I. (Frontiers in Physiology, 2022)
Stress can have a significant impact on many aspects of an organism’s physiology and behavior. However, the relationship between stress and regeneration, and how this relationship changes with age remains poorly understood. Here, we subjected young and old zebrafish to a chronic stress protocol and evaluated the impact of stress exposure on multiple measures of zebrafish behavior, specifically thigmotaxis (open field test) and scototaxis (light/dark preference test), and on regeneration ability after partial tail amputation. We found evidence that young and older adult fish are differentially impacted by stress. Only young fish showed a significantly greater change in anxiety-like behaviors after being exposed to chronic stress, while their regeneration ability was not affected by the stress protocol. On the other hand, older fish regenerated their caudal fin significantly slower compared to young fish, but their behavior remained unaffected after being exposed to stress. We further investigated the molecular mechanisms explaining the impact of stress exposure on regeneration in older fish by studying the changes in the expression of two gene candidates, nlgn1 and sam2 in the brain. We provide evidence that young and older adult fish are differentially impacted by stress. Young fish showed a greater change in anxiety-like behaviors than older fish after being exposed to chronic stress, while their regeneration ability was not affected by the stress protocol. On the other hand, older fish regenerated their caudal fin significantly slower compared to young fish, but their behavior remained unaffected after being exposed to stress. The expression of stress-related gene candidate sam2 increased in the brain of older individuals exposed to stress. Our results suggest there is a close relationship between chronic stress, regeneration, and behavior in zebrafish (Danio rerio), and that the impact of stress is age-dependent.